Pengaruh Pendidikan Kesehatan dengan Media Poster terhadap Pengetahuan dan Kesiapan dalam Menghadapi Menarche dan Pubertas: The Influence of Health Education with Poster Media on Knowledge and Readiness in Facing Menarche and Puberty - Anggraini, Yulida; Lestari, Ana; Rafi’ah, Rafi’ah (Chakra Brahmanda Lentera Institute, 2025)
Puberty is a crucial phase in adolescent life, marked by psychological and physiological changes, including menarche as the first menstruation. Lack of knowledge may cause anxiety in adolescent girls. Appropriate health education is needed to increase readiness for these changes. This study used a pre-post test one group design combined with a cross-sectional approach. A total of 67 fifth and sixth-grade female students from SDN 02 Labuhan Sumbawa participated. The intervention involved education using poster media, assessed using pre and post questionnaires. Data were analyzed using Paired t-test with a significance level of p < 0.05. The mean score of knowledge and readiness regarding menarche increased from 3.01 ± 1.562 to 8.55 ± 1.049. For puberty, it increased from 3.34 ± 1.657 to 7.78 ± 1.346 after the intervention. There was a significant difference before and after the intervention (p = 0.000, p < 0.05). : Poster media proved effective as a visual educational tool that enhanced students' understanding and readiness for menarche and puberty. Visualized information supports better retention and comprehension among young students. Health education using posters significantly improves knowledge and readiness of elementary school girls in facing menarche and puberty. Poster media is recommended as an efficient educational strategy in schools.